2020
DOI: 10.1007/978-3-030-43469-4_7
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Hyperprior Distributions to Estimate Variance Components for Interrater Reliability Coefficients

Abstract: UvA-DARE (Digital Academic Repository) Comparing hyperprior distributions to estimate variance components for interrater reliability coefficients ten Hove, D.; Jorgensen, T.D.; van der Ark, L.A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The code includes functions to estimate ICCs by means of maximum likelihood estimation (MLE) using the R package lme4 (Bates et al, 2015) or Markov chain Monte Carlo (MCMC) estimation using the R package brms (Bürkner, 2017), and is accompanied by example data-mimicking the design of Example 3-and example analyses of these data using both estimation methods. For more information about the MCMC method, we refer to Ten Hove et al (2020, 2021, and for more information about the MLE estimation method we refer to work by Jiang (2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The code includes functions to estimate ICCs by means of maximum likelihood estimation (MLE) using the R package lme4 (Bates et al, 2015) or Markov chain Monte Carlo (MCMC) estimation using the R package brms (Bürkner, 2017), and is accompanied by example data-mimicking the design of Example 3-and example analyses of these data using both estimation methods. For more information about the MCMC method, we refer to Ten Hove et al (2020, 2021, and for more information about the MLE estimation method we refer to work by Jiang (2018).…”
Section: Discussionmentioning
confidence: 99%
“…The MCMC and MLE estimation methods we provide on the OSF were shown to yield similar point estimates (Ten Hove et al, 2021). The MCMC estimation readily provides credible intervals for the ICCs (see, e.g., Ten Hove et al, 2020, 2021. The MLE-estimation method is supplemented with Monte-Carlo based confidence intervals that are specifically useful for coefficients such as ICCs (i.e., functions of parameters whose sampling distributions cannot be expected to be normal; cf.…”
Section: Guidelines On Selecting An Icc For Irr 11mentioning
confidence: 92%
See 1 more Smart Citation
“…The kurtosis ( 6 d f −4 ) is undefined due to division by 0 (thus approaches infinity in the limit), making it less restrictive than a truncated normal distribution about values being much larger than the mean. Simulation research has shown that this prior works well in variance-decomposition models [77], and it is the default prior for scale parameters in the R package brms [78]. Stan provides location (µ) and scale (σ) parameters, to center the t distribution at a different mean or to have greater variance.…”
Section: Stage 1: Estimate Multivariate Srm Parametersmentioning
confidence: 99%